2016
DOI: 10.6000/1929-4409.2016.05.16
|View full text |Cite
|
Sign up to set email alerts
|

Positive Criminology and Rethinking the Response to Adolescent Addiction: Evidence on the Role of Social Support, Religiosity, and Service to Others

Abstract: Adolescent addiction has emerged as a major public health problem. The greatest increase in alcohol and other drug use disorders can be found among youth. Concurrently, technological advances in policing coupled with aggressive prosecuting and sentencing practices have contributed to the growth of America’s correctional system. The assertive response of policing, courts, and corrections, however, have not prevented the dramatic rise of adolescent addiction. Unfortunately, there is no national data tracking add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 61 publications
(43 reference statements)
0
8
1
Order By: Relevance
“…Evidence-based studies have found that youths who are spiritually active, participate in a faith community, and invest in a prayerful relationship with their God are less likely to use or abuse drugs and alcohol and engage in related criminal activity (Johnson et al 2015, 2016a, b; Lee et al 2014, 2017; Post et al 2015, 2016). A seminal 2-year study by The National Center on Addiction and Substance Abuse (2001) at Columbia University, directed by Joseph A. Califano Jr., the former US Secretary of Health, Education, and Welfare in the Clinton administration, found that the teens who did not consider religious beliefs important were almost three times more likely to smoke, five times more likely to binge on alcohol, and almost eight times more likely to use marijuana compared with the teens who strongly appreciated the significance of religion in their daily lives.…”
Section: Sections Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence-based studies have found that youths who are spiritually active, participate in a faith community, and invest in a prayerful relationship with their God are less likely to use or abuse drugs and alcohol and engage in related criminal activity (Johnson et al 2015, 2016a, b; Lee et al 2014, 2017; Post et al 2015, 2016). A seminal 2-year study by The National Center on Addiction and Substance Abuse (2001) at Columbia University, directed by Joseph A. Califano Jr., the former US Secretary of Health, Education, and Welfare in the Clinton administration, found that the teens who did not consider religious beliefs important were almost three times more likely to smoke, five times more likely to binge on alcohol, and almost eight times more likely to use marijuana compared with the teens who strongly appreciated the significance of religion in their daily lives.…”
Section: Sections Of the Studymentioning
confidence: 99%
“…Since volunteering and helping others are associated with positive health outcomes (Yeung et al 2017), substance abuse recovery programs dependent on volunteering, such as those offered in A.A. and congregation-based groups, have a built-in advantage for success. More specifically, volunteering and helping others is found to be instrumental in addiction recovery (Lee et al 2016; Johnson et al 2016a, b; Pagano et al 2015; Post et al 2015, 2016). From the perspective of social identity theory (Dingle et al 2015), recovery is aided, and perhaps necessitated, by the presence of a consistent reference group of individuals who can help patients reconstruct their new identity as “nondrinking alcoholics,” that is, someone who is prone to abuse alcohol but decidedly no longer drinks (Borkman 2008).…”
Section: Sections Of the Studymentioning
confidence: 99%
“…However, there is growing awareness among clinicians and researchers that “spiritual virtues” (such as helping others and the experience of spiritual love), and religiosity more generally, are associated with improved sobriety and character development, as well as reduced recidivism (Johnson, Lee, Pagano, & Post, 2016; Kelly, Pagano, Stout, & Johnson, 2011; Lee & Pagano, 2014; Lee et al, 2016; Lee, Veta, Johnson, & Pagano, 2014). The recent establishment of the field of “positive criminology” has helped draw attention to the substantial secular and faith-based infrastructure that could be more fully utilized to improve adolescent recovery and character development, including the 12-Step program and support network originally developed in the 1930s by Alcoholics Anonymous (AA; see Johnson et al, 2016).…”
mentioning
confidence: 99%
“…As part of the interviews, we first tried to get a detailed description of the programs. Next, we asked the rabbis how, in their view, Judaism could serve as a platform for the rehabilitation of prisoners, both at the individual, social and spiritual levels according to the ideas offered by positive criminology and how it is implemented within the religious programs (Elisha, Ididis, and Ronel, 2012;Johnson, Lee, Pagano, and Post, 2016;Ronel, 2015;Ronel and Ben-Yair, 2017).…”
Section: Methodsmentioning
confidence: 99%